Is Sex as a Biological Variable Still Being Ignored in Preclinical Aging Research?. Issue 11 (17th February 2022) - Carmody, Colleen; Duesing, Charlotte G; Kane, Alice E; Mitchell, Sarah J
Abstract: Five years ago, the National Institute of Health (NIH) introduced a mandate to revolutionize the way sex as a biological variable (SABV) is considered in NIH-funded preclinical research. Given the known effects of sex on aging physiology, pathology, treatment response, and the effectiveness of interventions it is particularly important that SABV be considered in basic biology of aging research. Five years after this mandate, a significant amount of published work funded by the National Institute on Aging (NIA) is still not including mice of both sexes and/or not considering sex differences or comparisons in preclinical studies. Here we review a cross-section of recently published NIA-funded research to determine adherence to this mandate. We discuss the state of the preclinical aging field in terms of SABV and suggest strategies for improving adherence to the NIH mandate. It is imperative that we consider SABV and include males and females in all aspects of aging biology research to improve health outcomes for all.